In situ spatiotemporal mapping of 3-hydroxy-3-methylglutaryl-CoA reductase (HMGCR) inhibitor in pineapple (Ananas comosus) fruit tissue by MALDI mass spectrometry imaging - Suarez, Angelica Faith L.; Juanillo, Angel Ann B.; Sison, Dave Clark D.; Orajay, Joey I.; Javier, Maria Bella B.; Baladjay, Diane Monique S.; Yang, Yu-Liang; Saludes, Jonel P.; Dalisay, Doralyn S. (Frontiers in Natural Products, 2023)
Pineapple (Ananas comosus) fruit is a functional food that has become a part of healthy diets worldwide due to its nutrition and health benefits. Given this concept, the potential anti-hypercholesterolemic activity of pineapple fruit was assessed using in vitro HMG-CoA reductase (HMGCR) inhibition assay. Our findings show that pineapple fruit (PAF) extract showed HMGCR inhibition activity. These findings led to partial purification of PAF extract by gel filtration chromatography (GFC) whereby fraction PAF 06 exhibited 100.00% HMGCR inhibition at 10 mg/mL. Matrix assisted laser desorption ionization (MALDI) mass spectrometry profiling, HRMS, MS/MS, and dereplication identified N1,N10-diferuloylspermidine as potential HMGCR inhibitor in pineapple fruit. The MALDI mass spectrometry imaging (MSI) enabled the in situ spatiotemporal mapping of the HMGCR inhibitor, N1,N10-diferuloylspermidine, in the pineapple fruit tissue, with localization concentrated mainly in the tissue near the peel/shell and a gradual decrease towards the flesh and ovary. The MALDI MSI provided the first evidence of in situ spatial localization of N1,N10-diferuloylspermidine, a potential HMGCR inhibitor in pineapple while maintaining the cellular and structural features of the fruit tissues.